Studies of Peruvian Ptiliidae (Coleoptera) 4: Peruvium a new subgenus of Ptenidium with seven new species - Darby, Michael (Zootaxa, 2016)
Peruvium a new subgenus of Ptenidium Erichson with seven new species: P. brevissimum sp. n.; P. carinatum sp. n.; P. capillatum sp. n.; P. contractum sp. n.; P. gibbosum sp. n.; P. inornatum sp. n. and P. grande sp. n. is described and figured. The insects were collected by Dr Caroline Chaboo and her students at the University of Kansas as part of a programme to compile an inventory of leaf beetles in Peru and are the first records of Ptenidium from the country. A key is provided.